STUDY OF THE MANAGERIAL EFFECTIVENESS OF AUTHORITARIAN AND TOTALITARIAN REGIMES - Palii , Oleksandr (Public Management and Policy, 2026)
This article reviews key works that investigate the managerial efficiency of totalitarian and authoritarian regimes. The article also explores the main set of ideas regarding the reasons for the functional efficiency of totalitarian and authoritarian regimes. The article explores ideas regarding the efficiency of totalitarian and authoritarian regimes in times of crisis, military operations, mobilizations, etc., their ability to quickly make risky decisions, the ability to massively and immediately redistribute resources, direct the budget to strategic sectors, forcibly mobilize labor, material and scientific resources, ensure the predictability of the political process, which achieves high administrative manageability. On the other hand, the main ideas regarding the problems of the stability of authoritarian and totalitarian regimes and their vulnerability in terms of efficiency are presented. Thus, this article provides an overview of the main ideas that allow for a deeper analysis of the phenomenon of managerial efficiency of totalitarian and authoritarian regimes. At the same time, this article helps to understand the fundamental weakness of totalitarian regimes, which stems from their strength. This weakness, in particular, lies in the inability to ensure the full functioning of market mechanisms, which remain distorted. Quite often, totalitarian and authoritarian regimes make irrational economic decisions associated with the illusion of omnipotence. The problem is sometimes simply obtaining realistic statistical data by such regimes and understanding the objective state of affairs in the country by the authorities, given the reign of fear among the bureaucracy and the formation of a culture of false reporting. Corruption and favoritism can form a wave of ineffective decisions, determined by purely subjective things. In addition, in democratic political regimes, such mistakes are usually easier to correct under public pressure or election cycles. At the same time long existence of totalitarian and authoritarian regimes, their ability to survive and to overcome crises through centralization, more effective mobilization of resources and achieving regime integrity through suppression of social alternatives, does not allow to underestimate the potential for the stability of such regimes and their high competitiveness even in comparison with powerful developed democratic states. The ability of totalitarian and authoritarian regimes to adapt and maintain their authoritarian and totalitarian nature under the guise of formal changes and purely ritual pseudo-democratic electoral processes requires special further study.